Helicobacter pylori eradication lowers serum homocysteine level in patients without gastric atrophy - Ozer, Birol (World J Gastroenterol, 2005)
AIM: To determine whether Helicobacter pylori (H pylori)infection caused hyperhomocysteinemia by altering serum vitamin B(12), serum folate and erythrocyte folate levels and whether eradication of this organism decreased serum homocysteine level. METHODS: The study involved 73 dyspeptic H pylori-positive patients, none of them had gastric mucosal atrophy based on rapid urease test and histology. Out of 73 patients, 41 (56.2%) showed a successful eradication of H pylori 4 wk after the end of treatment. In these 41 patients, fasting serum vitamin B(12), folate and homocysteine levels, and erythrocyte folate levels before and 4 wk after H pylori eradication therapy were compared. RESULTS: The group with a successful eradication of H pylori had significantly higher serum vitamin B(12) and erythrocyte folate levels in the post-treatment period compared to those in pre-treatment period (210±97 pg/mL vs 237±94 pg/mL, P<0.001 and 442±212 ng/mL vs 539±304 ng/mL, P = 0.024, respectively), but showed no significant change in serum folate levels (5.6±2.6 ng/mL vs 6.0±2.4 ng/mL, P = 0.341). Also, the serum homocysteine levels in this group were significantly lower after therapy (13.1±5.2 μmol/L vs 11.9±6.2 μmol/L, P = 0.002). Regression analysis showed that serum homocysteine level was positively correlated with age (P = 0.01) and negatively with serum folate level before therapy (P = 0.003). CONCLUSION: Eradication of H pylori decreases serum homocysteine even in patients who do not exhibit gastric mucosal atrophy. It appears that the level of homocysteine in serum is related to a complex interaction among serum vitamin B(12), serum folate and erythrocyte folate levels.